Analisis Viktimologis Pelecehan Seksual Verbal di Wilayah Hukum Kota Malang (Studi di Polresta Kota Malang) - Dandi Juliantara; Haris Thofly; Nu'man Aunuh (Indonesia Law Reform Journal, 2021)
Verbal sexual abuse in the form of body comments, whistles, kisses, flirting, racist comments, and gestures that lead to sexual context. There are many cases of verbal sexual abuse that occur in the jurisdiction, especially in Malang City. Data owned by the authors based on interviews and questionnaires to 19 respondents 73.7% of whom had experienced verbal sexual abuse in Malang City. The incident took place on public roads, coffee shops, and work environments. This research is a sociological juridical study with primary data (interview and kuseioner), secondary data (scientific articles or scientific works and laws and regulations). The results of this study show that, victims of verbal sexual abuse in the jurisdiction of Malang City who suffered psychological losses have not been entitled to legal protection against themselves, broadly explained in the Witness and Victim Protection Act and the Human Rights Act which explains that victims are entitled to personal protection, security and comfort in the jurisdiction of Malang City. The constraints of the Malang City Police are related to the substance of the law that has not specifically regulated verbal sexual abuse, but law enforcement officials have tried to provide preventive and repressive efforts to prevent verbal or non-verbal sexual abuse. Keywords: Sexual Harassment; Protection; Victim. Abstrak Pelecehan seksual verbal dalam bentuk komentar atas tubuh, siulan, suara kecupan, main mata, komentar rasis, dan gestur tubuh yang mengarah pada konteks seksual. Terdapat banyak kasus-kasus pelecehan seksual secara verbal yang terjadi di wilayah hukum khususnya di Kota Malang. Data yang dimiliki penulis berdasarkan wawancara dan kuesioner terhadap 19 responden 73,7% diantaranya pernah mengalami pelecehan seksual verbal di Kota Malang. Kejadian tersebut terjadi di jalan umum, kedai kopi, dan lingkungan pekerjaan. Penelitian ini merupakan penelitian yuridis sosiologis dengan data primer (wawancara dan kuseioner), data sekunder (artikel ilmiah atau karya ilmiah dan peraturan perundang-undangan). Hasil penelitian ini menujukkan bahwa, Korban pelecehan seksual secara verbal di wilayah hukum Kota Malang yang mengalami kerugian secara psikis belum mendapatkan haknya berupa perlindungan hukum terhadap dirinya, secara garis besar dijelaskan dalam Undang-Undang Perlindungan Saksi dan Korban serta Undang-Undang Hak Asasi Manusia yang menjelaskan  bahwa korban berhak mendapatkan perlindungan pribadi, rasa aman dan kenyaman di wilayah hukum mengatur pelecehan seksual secara verbal, namun aparat penegak hukum telah berupaya memberikan upaya preventif dan represif guna mencegah pelecehan seksual verbal atau non verbal.